Sistem pengurusan kemudahan sekolah / Lok Farn - Lok , Farn (2001)
Facility Management System (FMS) is a window-based system developed with the objectives of implementing the task of daily operation needs of small to medium size secondary school. It supports the inventory, usage and maintenance tracking, booking functionality of a typical secondary school. To maximize the effectiveness, FMS provides a computerized interface that greatly simplify information generation which enables decision maker to creatively approach, analyze and uncovering transaction problems and opportunities. Since the local architecture forms the core of the system, research was conducted into the local computing concepts. Through the course of FMS development, it is proven that management rules can be encapsulated into the local information system. The prototyping approach is selected for the development process of FMS since it supports rapid application development and reduces the unforeseen risks. Software engineering principles are applied throughout the development phases of system analysis, design, testing and implementation. FMS is developed using Visual Basic 6.0, an object oriented and visual-programming language on the Windows platform utilizing data base created and stored by Microsoft Access 97. It is believed that this system can be migrated to on-line data base information system in future. Finally, problems are inevitably encountered due to the complexity and fast changing of various aspects of system requirement, techniques and solutions are used to address these problems. Although, FMS limited in certain aspects, it serves as a foundation for the future development of similar systems.